2011
DOI: 10.1007/s10719-011-9328-3
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation of ovomucin from hen egg white

Abstract: Ovomucin is a bioactive egg white glycoprotein responsible for the gel properties of fresh egg white and is believed to be involved in egg white thinning, a natural process that occurs during storage. Ovomucin is composed of two subunits: a carbohydrate-rich β-ovomucin with molecular weight of 400-610 KDa and a carbohydrate-poor α-ovomucin with molecular mass of 254 KDa. In addition to limited information on O-linked glycans of ovomucin, there is no study on either the N-glycan structures or the N-glycosylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 45 publications
1
46
1
Order By: Relevance
“…The region detected on chromosome 7 between positions 23 and 30 Mb seems to be important for egg quality traits and includes a cluster of cell shape and adhesion genes, such as ITGB3 ( integrin, beta 3 (platelet glycoprotein IIIa, antigen CD61), 23.38 Mb), DES ( desmin, 23.73 Mb), VIL1 ( villin 1, 24.09 Mb), TNS4 ( tensin 4, 24.09 Mb), ITGB5 (integrin, beta 5 , 29.46 Mb) and MUC13 ( mucin 13, cell surface associated, 29.51 Mb). In particular, MUC13 is a very attractive candidate for controlling albumen quality because the ovomucin protein, consisting of mucin subunits, is believed to be responsible for the gel-like structure of the fresh albumen [16,17,28,32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…The region detected on chromosome 7 between positions 23 and 30 Mb seems to be important for egg quality traits and includes a cluster of cell shape and adhesion genes, such as ITGB3 ( integrin, beta 3 (platelet glycoprotein IIIa, antigen CD61), 23.38 Mb), DES ( desmin, 23.73 Mb), VIL1 ( villin 1, 24.09 Mb), TNS4 ( tensin 4, 24.09 Mb), ITGB5 (integrin, beta 5 , 29.46 Mb) and MUC13 ( mucin 13, cell surface associated, 29.51 Mb). In particular, MUC13 is a very attractive candidate for controlling albumen quality because the ovomucin protein, consisting of mucin subunits, is believed to be responsible for the gel-like structure of the fresh albumen [16,17,28,32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, ovalbumin and ovomucoid are the major glycoproteins in hen's egg white, but the oligosaccharides of ovalbumin comprise three high-mannose type oligosaccharides (Man5, Man6 and Man7) and a series of hybrid type glycans, [18][19][20] whereas ovomucoid contains complex-type glycans with an increased number of antennae. 21 These variations make it difficult to predict the structure of glycans based on information about their source.…”
Section: ·1 N-linked Oligosaccharides (Asn Type Glycans)mentioning
confidence: 99%
“…Partial amino acid sequencing and analysis of the peptides of the preparation indicated that it was indeed similar to alpha-ovomucin. It was reported that beta-ovomucin is carbohydrate-rich with approximately 60% carbohydrates [26], and it is very difficult to digest the beta-ovomucin by trypsin without deglycosylation. Thus, limited peptides information about the betasubunit was found in the MS analysis.…”
Section: Influence Of Mgcl 2 Concentrations On the Isolation Of Ovomucinmentioning
confidence: 99%
“…The maximum yield was observed at a salt concentration of 500 mM, followed by 50 mM NaCl concentration (P < 0.05). Yields of ovomucin prepared by different researchers are not comparable, because the yield is affected by many other variables except the preparation method, such as egg sources, freshness and measuring methods [26,27].…”
Section: Influence Of Mgcl 2 Concentrations On the Isolation Of Ovomucinmentioning
confidence: 99%